Response of corn genotypes to weed interference and nitrogen in Nigeria - Chikoye, David; Lum, A.F.; Abaidoo, Robert C.; Menkir, A.; Kamara, A.; Ekeleme, F.; Sanginga, Nteranya (Cambridge University Press, 2008)
The effects of nitrogen (N) rate and weed interference on the grain yield of four corn genotypes were investigated in 2002 and 2003 at Ikenne (7u389N, 3u429E), Shika (11u119N, 7u389E), and Samaru (10u249N, 7u429E) in Nigeria. Nitrogen (N) at 0, 30, 60, and 90 kg N ha21 were the main plot treatments. Weed-free (weeded weekly), low (intrarow weeds only), and high (zero weeding) weed pressure were the subplot treatments. Four corn genotypes (ACR8328 BN C7, Low-N-Pool C2, Oba Super II, TZB-SR) were the sub-subplot treatments. Weed density was higher at Shika and Samaru than at Ikenne, and the order of average weed biomass 8 to 10 weeks after planting was Samaru (271 g m22) . Ikenne (236 g m22) . Shika (161 g m22). Corn genotype and N rate had no effect on weed biomass except at Samaru where fertilized treatments had higher weed biomass than the unfertilized treatments. Corn leaf area (LA) increased with increasing N rate at all locations regardless of weed pressure and genotype, except at Shika where ACR8328 BN C7, Oba Super II, and TZBSR did not show any clear N response; LA was highest in the weed-free and lowest in the unfertilized treatments for all genotypes and locations, and weed pressure treatments. Low-N-Pool C2 had the highest LA, which was 1.3 times larger than in Oba Super II, which had the lowest LA. Nitrogen rate, weed pressure, and genotypes significantly affected corn leaf chlorophyll content. Chlorophyll content was higher in the fertilized treatments than the unfertilized treatments, and higher in the weed-free treatments than the low or high weed pressure treatments. ACR8328 BN C7 and Oba Super II had significantly more chlorophyll than the other genotypes. Low-N-Pool C2 showed a linear grain yield response with the increase in N rates. ACR8328 BN C7 did not respond to N application. Compared with the results in the weed-free treatment, high weed pressure reduced grain yield in all genotypes by more than 65% at Samaru, 50% at Shika, and 35% at Ikenne.